PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE TRUE OR FALSE UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN TEKS EKSPOSISI KELAS X MIPA 1 SMA NEGERI 2 PEKANBARU: Applying True or False Active Learning Strategies to Increase Students ’Learning Outcomes in the Topic of Text Exposition of Class X MIPA 1 SMA Negeri 2 Pekanbaru - Nurmaini, Nurmaini (Perspektif Pendidikan dan Keguruan, 2018)
Learning is a system that aims to help the learning process of students, which contains a series of events that are designed, arranged in such a way as to influence and support the learning process of students (Firdaus, 2012). According to Nasution (2000) the learning process is an interaction / process of communication between the teacher and students and between students and students. Intertwined communication should be reciprocal communication created in such a way, so that the message conveyed in the form of the subject matter will be effective and efficient. Students as the subject of learning must play an active role in learning. the activeness of students is assessed from their role in learning, such as asking questions, answering questions, giving responses and others. In addition, the activeness of students is a form of independent learning, namely students trying to learn everything about their own will and ability / business, so that in this case the teacher only acts as a mentor, motivator and facilitator. Therefore, the teacher needs to create an atmosphere of learning that can foster an attitude of collaboration between students and other students. The main problem in learning in formal education (school) today is the low absorption of students. The learning process to this day is still dominated by teachers and does not provide access for students to develop independently through discovery in the process of thinking. According to Dimyati and Mudjiono (2002) the dominance of teachers in the learning process causes students to be passively involved, students are more waiting for the presentation of the teacher rather than looking for and finding their own knowledge, skills and attitudes they need during the learning process. Therefore, it is necessary to apply new learning strategies that can make students actively participate in learning. One active learning strategy developed by Silberman (2011) is true or false active learning strategies. The learning steps in the true or false active learning strategy will activate students from the beginning of learning which will stimulate students to think and motivate students to play an active role in learning activities so that the teacher does not dominate the learning process. This strategy is marked by the teacher making statements that are in accordance with the subject matter, half right and the other half wrong. Then students discuss in their groups to state whether the statement is true or false. By discussing students can exchange opinions. According to Silberman (2011) by listening to various opinions, students will be challenged to think. our brain will do a better learning process if we discuss information with other people. When the learning process is passive, the brain cannot store information properly. In answering questions, students are required to give reasons why they answer correctly and why they answer wrongly. This is so that students do not guess when answering and will make students better understand the material. Then the results of the group discussion will be presented in front of the class, students are given the opportunity to ask questions, answer questions and respond or give opinions. This will activate students more in learning and can train students' courage. According to Silberman (2011), learning activities carried out with the activities of students themselves will cause a knowledge to be more meaningful and can last a long time in memory of students so that the learning outcomes achieved will be better. Based on the results of the study obtained values from the first and second cycles in a row - according (77.33%), and (80.00%).